Faktor-Faktor yang Memengaruhi Implementasi Program Kampung Iklim di Desa Pandean Kecamatan Ngablak Kabupaten Magelang - Rizal Aziz Anugerah; Jona Bungaran Basuki Sinaga (Jurnal Kebijakan Pemerintahan, 2025)
Climate change is a global environmental challenge that directly impacts the sustainability of human life, including in Indonesia. Although the government has implemented various adaptation and mitigation programs, implementation at the local level often faces obstacles such as poor communication between stakeholders, limited resources, and weak bureaucratic support and a weak policy environment. The research method used was inferential quantitative with purposive sampling, involving 98 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with t test, F test, and coefficient of determination (R²) through SPSS 27. The results showed that the variables of communication, resources, executor attitude, bureaucratic structure, and policy environment had a significant effect on the implementation of Proklim, both partially and simultaneously. The Adjusted R² value of 0.870 indicates that 87% of the variation in Proklim implementation is explained by the independent variables, while 13% is influenced by other factors. The conclusion of this study confirms that the success of Proklim is highly dependent on effective communication, availability of resources, positive attitude of implementers, supportive bureaucratic structure, and conducive policy environment. Therefore, it is recommended that the village government improve coordination with the community and stakeholders. Keywors: communication, resources, implementer attitudes, bureaucratic structure, policy environment, Proklim implementation, environmental sustainability